Recent advances in multidisciplinary applied physics : proceedings of the First International Meeting on Applied Physics (APHYS 2003) October 13-18th, 2003, Badajoz, Spain - Mendez-Vilas, A. (Physica scripta (Stockholm, Sweden : 1982), 2005)
The 1st International Meeting on Applied Physics (APHYS-2003) succeeded in creating a new international forum for applied physics in Europe, with specific interest in the application of techniques, training, and culture of physics to research areas usually associated with other scientific and engineering disciplines. This book contains a selection of peer-reviewed papers presented at APHYS-2003, held in Badajoz (Spain), from 15th to 18th October 2003, which included the following Plenary Lectures: Nanobiotechnology - Interactions of Cells with Nanofeatured Surfaces and with Nanoparticles. Radiation Protection of Nuclear Workers - Ethical Issues. Chaotic Data Encryption for Optical Communications.